Evaluation on applying Condensate from Food Waste Dry Process as External Carbon Source to Biological Denitrification Process - Jae Hoon Jeung; Tae Young Kim; Yu Kyung Kim; Jea Jun Song; Soon Woong Chang; Woo Jin Chung (대한환경공학회지, 2022)
Objectives In this study, the applicability of dry condensate generated from food waste dry feed conversion process was evaluated as an external carbon source to increase the efficiency of the biological denitrification process. Methods The experiment was carried out in the form of a batch test, and dry condensate was injected into each reactor according to the COD and T/N ratio (C/N ratio). Then, the reactor was operated under anoxic conditions for 5 hours, and nitrate nitrogen was analyzed at intervals of 1 hour. Results and Discussion The dry condensate from food waste showed a low nitrogen content (T-N 220 mg/L) compared to a high organic matter content (TCOD 21,863 mg/L), and was analyzed to satisfy the conditions of an external carbon source in the denitrification process. And as a result of the experiment, it was found that the nitrate nitrogen removal efficiency was up to 76% after 5 hours at a C/N ratio 7.50:1, which was significantly increased compared to the control which was without condensed water (removal efficiency 4%). Moreover, the removal efficiency of 28% was exhibited even at the C/N ratio 0.95:1, which exhibited the lowest efficiency. In addition, as a result of calculating the specific denitrification rate (SDNR) for each C/N ratio, 7.50:1 was found to be as 0.0726 mg NO3-/mg VSS/d, which was significantly increased than that of control as 0.0038mg NO3-/mg VSS/d. Conclusion Based on these results, it is judged that it is possible to utilize the dried condensate of food waste as an external carbon source in the denitrification process.